Riparian Areas and Fine‐Scale Forest Cover and Structure Drive Occupancy Patterns of Sympatric Mustelids - Lauren Wheelhouse; Heather Bryan; Shannon Crowley; Chris Johnson; Dexter Hodder (Ecology and Evolution)
ABSTRACT Boreal and subboreal forests of western North America support diverse mesocarnivore populations with overlapping spatial, temporal, and dietary niches. However, interactions among these species and the factors influencing their co‐occurrence—such as population cycles, landscape changes, harvest mortality, and resource availability—are not well documented. We used 5 years (2015, 2016, 2020, 2021, and 2022) of data from remote cameras and fine‐scale habitat data from Light Detection and Ranging to assess patterns in the spatial co‐occurrence of short‐tailed weasel (Mustela erminea), American mink (Neogale vison), American marten (Martes americana), and fisher (Pekannia pennanti) in central British Columbia, Canada. We used multispecies occupancy models to test hypotheses about the relationships between mesocarnivore co‐occurrence and habitat. Mesocarnivores were more likely to co‐occur at sites closer to riparian zones and at sites with greater complexity of vertical forest structure. Short‐tailed weasel, however, did not co‐occur with other mustelids in riparian zones. Importantly, we found that habitat covariates associated with co‐occurrence were relatively similar over time despite changes in the abundance of predators and prey. Our findings highlight the importance of retaining riparian habitats and forest complexity as part of forest harvesting practices to promote species co‐occurrence.